Fenofibrate Reduces Mortality and Precludes Neurological Deficits in Survivors in Murine Model of Japanese Encephalitis Viral Infection - Sehgal, Neha; Kumawat, Kanhaiya Lal; Basu, Anirban; Ravindranath, Vijayalakshmi (PLOS ONE, 2012)
Background Japanese encephalitis (JE), the most common form of viral encephalitis occurs periodically in endemic areas leading to high mortality and neurological deficits in survivors. It is caused by a flavivirus, Japanese encephalitis virus (JEV), which is transmitted to humans through mosquitoes. No effective cure exists for reducing mortality and morbidity caused by JEV infection, which is primarily due to excessive inflammatory response. Fenofibrate, a peroxisome proliferator-activated receptor-α (PPARα) agonist is known to resolve inflammation by repressing nuclear factor-κB (NF-κB) and enhancing transcription of anti-oxidant and anti-inflammatory genes. In addition, fenofibrate also up-regulates a class of proteins, cytochrome P4504Fs (Cyp4fs), which are involved in detoxification of the potent pro-inflammatory eicosanoid, leukotriene B4 (LTB4) to 20-hydroxy LTB4. Methodology/Principal Findings The neuroprotective effect of fenofibrate was examined using in vitro (BV-2 microglial cell line) and in vivo (BALB/c mice) models of JEV infection. Mice were treated with fenofibrate for 2 or 4 days prior to JEV exposure. Pretreatment with fenofibrate for 4 but not 2 days reduced mortality by 80% and brain LTB4 levels decreased concomitantly with the induction of Cyp4f15 and 4f18, which catalyze detoxification of LTB4 through hydroxylation. Expression of cytokines and chemokine decreased significantly as did microglial activation and replication of the JEV virus. Conclusions/Significance Fenofibrate confers neuroprotection against Japanese encephalitis, in vivo, in mouse model of JEV infection. Thus, fenofibrate, a PPARα agonist that is commonly used as a hypolipidemic drug could potentially be used for prophylaxis during JE epidemics to reduce mortality and morbidity.